Euendolithic Cyanobacteria and Proteobacteria Together Contribute to Trigger Bioerosion in Aquatic Environments - Wu, Guimei; Huang, Aiyou; Wen, Yanhong; Wang, Hongxia; Wang, Jiangxin; Luo, Fuguang; Wu, Mingcan (Frontiers in Microbiology, 2022)
Shellfish, mussels, snails, and other aquatic animals become effective carbon sinks through carbon capture from water and carbon sequestration (shell formation), reducing the "greenhouse effect" gases in the atmosphere. However, bioerosion hinders this process (it erodes the CaCO3-shell, releasing CO2). The bioerosion of aquatic environments remains to be elucidated. In this present study, the bioerosion of Bellamya spp. snail shells from the aquatic environment were taken as the research object. In situ microbial community structure of the bioerosion shell from different geographical locations, laboratory-level infected culture, and validated experiments were studied by coupling traditional observation and 16S rRNA sequencing analysis method. This study found that these bioeroders could implant in the CaCO3 layer of the snail shell, many holes would occur. This made the density of the shell so lower that it could be broken easily. Interestingly, it found that bioeroders were distributed in the two taxonomic phyla Cyanobacteria and Proteobacteria. Further cluster analysis showed that Cyanobacteria sp. and two unidentified genera (Burkholderiaceae and Raistonia) were the key bioeroders. Moreover, the interaction of them promoted the biological function of "shell bioerosion" were confirmed using a filamentous, boring-shell cyanobacteria, named CSB03. This study identified the causes of "shell bioerosion" in aquatic environments and provided a theoretical basis for preventing and controlling "shell bioerosion" disease in the aquatic industry. Meanwhile, it provided new insights of cyanobacterial bioerosion of shells and microalgae carbon sequestration.